2019
DOI: 10.1002/stc.2465
|View full text |Cite
|
Sign up to set email alerts
|

Modified direct displacement‐based design approach for structures equipped with fluid viscous damper

Abstract: Summary Direct displacement‐based design (DDBD) approach is one of the most effective performance‐based design methods. In this paper, a modified version of DDBD is proposed for the design of structures equipped with fluid viscous damper (FVD) that the effect of higher modes and difference between spectral velocity and pseudo‐spectral velocity are applied in the design process. Different steel moment frames equipped with FVD have been designed using the proposed method, and the achievement of desirable perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…To achieve a well-designed FVD, the higher mode effects should be considered in the design process. Noruzvand et al (2020) proposed a modified version of DDBD with considering higher mode effects in the design process. They also applied the difference between spectral velocity and pseudo-spectral velocity in the design process of FVD.…”
Section: Classical Ddbd For Steel Moment-resisting Frame Controlled By Fvdmentioning
confidence: 99%
See 4 more Smart Citations
“…To achieve a well-designed FVD, the higher mode effects should be considered in the design process. Noruzvand et al (2020) proposed a modified version of DDBD with considering higher mode effects in the design process. They also applied the difference between spectral velocity and pseudo-spectral velocity in the design process of FVD.…”
Section: Classical Ddbd For Steel Moment-resisting Frame Controlled By Fvdmentioning
confidence: 99%
“…The design steps of DDBD developed in this study for steel moment-resisting frames controlled by linear FVD can be classified as shown in Figure 1. For comparison, DDBD approach modified by Noruzvand et al (2020) has been also reported. More details about these design steps and parameters can be found in Noruzvand et al (2020).…”
Section: Classical Ddbd For Steel Moment-resisting Frame Controlled By Fvdmentioning
confidence: 99%
See 3 more Smart Citations